PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION PADA POKOK BAHASAN BANGUN RUANG - Saputri, Anggi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research was aimed at improvingthe students’ mathematic problem solving competence through Problem-Based Instruction (PBI). The subject of this research was IV graders od SD Negeri 1 Kalibagor consisting of 18 males and 19 females. The design of this research was Classroom Action Research which was carried out in 2 cycles in which every cycle consisted of 2 meetings. In each cycle there were planning, acting, observing, and reflecting. The result of the research indicated that the implementation of learning mathematic through Problem- Based Instruction learning model could enhance the mathematic problem solving competence. This was proven by the increaseof the average score of mathematic problem solving competence. The average score inthe first cycle was 14.21 which was considered goog, and in the second cycle it was 16.69 which belonged to very good criteria. The average result of students’ mathematic problem soving competencetest was 71.03 in the first cycle and 83.51 in the second cycle. Furthermore, the students’ learning mastery was 51.40% in the first cycle and 89.19% in the second cycle whic indicated an improvement